Imagining that neoliberalism doesn’t exist: toward a feminist populism - Cadahia, Luciana (Scenari, 2021)
There seems to be a series of theoretical disagreements between feminism and populism that makes it difficult to think together these two forms of political struggle, creating a split that weakens the emancipatory force that organizes each one. As far as this intervention is concerned, I would like to explore a link between the two, in order to think whether something like a populist feminism or a feminist populism would be possible to imagine.